Signifikansi Pelatihan Baca Gali Alkitab di SMA Negeri 1 Sipora Mentawai Pada Semarak Ramadhan 2023 - Keluanan, Yane Henderina; Belo, Yosia; Moimau, Aprianus Ledrik; Sakerebau, Immerius; Manurung, Jendri Leddoin; Ginting, Gundari (Sekolah Tinggi Teologi Real Batam, 2023)
This activity was carried out at State High School Negeri 1 Sipora, in Sioban, Mentawai Regency, West Sumatra. The activity was given with the aim that the training participants, namely students, have a simple and practical understanding and method in understanding the message of the Bible. As a writing, the Bible certainly requires a way of understanding and finding the message contained in it. Because the writings in it are related to many things according to the context of authorship such as language, culture and habits, geography and even the purpose of the writing for early readers. Therefore, the Bible Reading Digging (BRD) training is considered necessary to be delivered to participants. The activity method uses the form of a workshop and begins with the presentation of BGA material and steps. During the training, participants seemed enthusiastic including timely arrival, passion for working in groups and presentation of group work results in a polite, calm and directed manner. Not to forget the role of the teachers who accompanied the group from start to finish so that participants in the group were more enthusiastic. As a result, the presentation of each group showed satisfactory results because the excavation carried out was in accordance with the BRD method taught. Trainees understand the methods provided and are able to do the task.Keywords: BRD; Sipora High School; Mentawai; Youth; BibleAbstrakKegiatan ini dilaksanakan di Sekolah Menengah Atas (SMA) Negeri 1 Sipora, di Sioban, Kabupaten Mentawai, Sumatera Barat. Kegiatan diberikan dengan tujuan agar peserta pelatihan yakni siswa-siswi memiliki pemahaman dan metode yang sederhana dan praktis dalam memahami pesan Alkitab. Sebagai suatu tulisan Alkitab tentu memerlukan cara memahami dan menemukan pesan yang ada di dalamnya. Sebab tulisan-tulisan di dalamnya terkait banyak hal sesuai konteks kepenulisan misalnya bahasa, budaya dan kebiasaan, geografi bahkan tujuan tulisan itu bagi pembaca awal. Karenanya pelatihan Baca Gali Alkitab (BGA) dipandang perlu disampaikan kepada peserta. Metode kegiatan menggunakan bentuk workshop dan diawali dengan pemaparan materi dan langkah-langkah BGA. Selama pelatihan peserta nampak antusias peserta diantaranya dengan kedatangan tepat waktu, gairah bekerja di kelompok serta presentasi hasil kerja kelompok dengan santun, tenang dan terarah. Tidak ketinggalan peran para Guru yang turut mendampingi kelompok dari awal hingga selesai sehingga peserta dalam kelompok kian semangat. Hasilnya, presentasi dari tiap kelompok menunjukkan hasil yang memuaskan karena penggalian yang dilakukan telah sesuai dengan metode BGA yang diajarkan. Peserta pelatihan memahami metode yang diberikan dan mampu mengerjakan tugas.Kata Kunci: BGA; SMA Sipora; Mentawai; Pemuda; AlkitabÂ